Impact of Chlorhexidine Gluconate Intolerance on Driveline Infection during Chronic Heartmate II Left Ventricular Assist Device Support. Issue 11 (November 2016) - Son, Andre Y.; Stein, Louis H.; DeAnda, Abe; Katz, Stuart D.; Smith, Deane E.; Reyentovich, Alex; Balsam, Leora B.
Purpose: Driveline exit site (DLES) management following left ventricular assist device implantation is important for preventing driveline infection (DLI). While chlorhexidine gluconate (CHG) is generally recommended for DLES antisepsis, CHG intolerance can develop, resulting in a need for alternative antiseptics. We reviewed our institutional experience with DLES antisepsis methods in HeartMate II patients, comparing outcomes of patients with and without CHG intolerance. Methods: Between October 2011 and March 2016, 44 patients underwent primary HeartMate II implantation. CHG was used for DLES antisepsis and povidone-iodine (PVP-I) was used in patients with CHG intolerance. DLI was defined by Interagency Registry for Mechanically Assisted Circulatory Support (INTERMACS) criteria. Results: Of 44 patients, 37 (84%) received CHG and 7 (16%) received PVP-I antisepsis due to CHG intolerance. Five patients (11.4%) developed a DLI, with an event per patient-year rate of 0.07. Median length of support was 521 days (interquartile range 202–881 days). Characteristics were similar between patients with and without DLI. However, a larger proportion of patients with DLI had CHG intolerance compared to patients without DLI (60.0% vs. 10.3%, p<0.05). Causative organisms were Staphylococcus aureus in CHG-intolerant patients and Stenotrophomonas and Acinetobacter in CHG-tolerant patients. Kaplan-Meier method and log-rank test demonstrated decreased infection-free days in patients using PVP-I rather than CHG (p<0.01). Conclusions: While the etiology of DLI is multifactorial, CHG intolerance appears to be a risk factor. Our findings highlight the need for larger studies comparing the efficacy of antiseptics for DLES care, particularly for patients with CHG contraindications.